Chuan Leekpai [Thailand, Prime Minister] - Chuan, Leekpai (Institutional Knowledge at Singapore Management University, 2015)
Chuan Leekpai is a two-time Thai Prime Minister. He shares with DNA the thinking behind some of his policies, as well as gives his take on the recent political turmoil Thailand has been embroiled in.